Labor unions and institutional corruption: The case of Kazakhstan - Slyamzhar Akhmetzharov (SAGE Publishing, 2021)
In this study, we used the institutional corruption framework to analyze the evolution of labor unions in Kazakhstan. As a research method, we conducted a case study by combining document analysis with survey data covering (n)1,200 respondents across all 14 regions of the country. Our findings suggest that external and internal influences weakened labor unions and diverted from fulfilling their primary purpose of promoting interests of their members. External influences, represented by restrictive regulatory framework and state intervention, create conditions of limited independence of labor unions leaving them extremely narrow scope to operate in. Internal influences are represented by disagreements and conflicts between national-level labor unions. This article stipulates that dysfunctional and institutionally corrupt labor unions in Kazakhstan serve as an indicator of state fragility. The findings confirmed that institutional corruption of labor unions has an adverse impact on public trust, while a frequent occurrence of labor conflicts might impact political risk factors, contributing to increased state fragility.